Effects of Sub1 and qDTY on the agro-morpho-physiological traits of rice (Oryza sativa L.) under reproductive stage drought stress - Shakirah Mohammad Nahar,; Nur Sakinah Mohd Yusri,; Asmuni Mohd Ikmal,; Noraziyah Abd Aziz Shamsudin,; Siti Nurfaeiza Abd Razak,; Pui, Maggie San Sudo; Song, Beng-Kah; Bey, Hing Goh; Long, Chiau Ming (Penerbit Universiti Kebangsaan Malaysia, 2024)
Drought is one of the major abiotic stresses that affects plants at various levels and stages as it also reduces crop productivity and weakens global food security. Breeding and screening of drought tolerant varieties are crucial to ensure the continuity of food supply. Two breeding lines, UKM-112 and UKM-114 with QTL(s) for submergence tolerance (Submergence 1 [Sub1]) and yield under drought stress (qDTY) and together with their recurrent parental line, UKM-5, and a drought-sensitive cultivar, MR219 were screened for their agro-morpho-physiological responses under reproductive stage drought stress (RS) and non-stress (NS) to determine how the Sub1 interacts with qDTY in enhancing drought tolerance. Under NS, UKM-112 (with qDTY3.1 and Sub1) recorded the highest values while MR219 (no QTL) recorded the lowest values for most parameters. Furthermore, lines with QTL (either single or two QTLs) outperformed MR219 in all agronomic parameters including grain yield (GY) under RS. UKM-114, which carries the Sub1, demonstrated higher values for important agronomic traits such as the number of filled spikelets (FS), thousand-grain weight (TGW), and GY when exposed to drought stress. The enhanced values in UKM-114 are a good indication that the presence of Sub1 minimized the negative impacts of drought on yield-related traits. The genotype with qDTY or a combination of qDTY and Sub1 has a lower photosynthetic rate under RS compared to the genotype with only Sub1 but higher than MR219 suggesting that qDTY improved the photosynthetic rate, though lesser compared to Sub1. These results indicate that Sub1+qDTY does not effectively improve drought stress survivability and yield. The presence of qDTY appears to mask the beneficial effect of Sub1 in improving photosynthetic rate and yield. While the present study did not report a positive outcome for Sub1+qDTY, the combination of these traits has the potential to provide beneficial effects without any negative interactions.